INTRODUKSI MANAJEMEN AYAM PETELUR SISTEM KANDANG TERTUTUP (CLOSED HOUSE) DI SAREE - ACEH - Edy Fradinata,; Aman Yaman,; Dasrul, Dasrul; Fauzi Umar, (JURNAL PENGABDIAN MANDIRI, 2022)
Closed House Chicken Cage is a closed cage system that is able to help optimize environmental conditions including windows, temperature & humidity. With a Closed House cage, there is stable air movement and the humidity level in the cage can be adjusted according to the needs of the chicken. Aceh as an egg supplier area from Medan Province has to start slowly releasing this dependence. The need for eggs for the Aceh region per day can reach 1-2 million eggs. Seeing such a lucrative market, it is appropriate for Aceh to have a laying hens farming system that is automatic and close in nature, so that it will produce more eggs and remain in number. The UPTD of the Aceh Livestock Service has developed laying hens with a Close House system built in 2017 which is located in a saree. And in Blang Bintang, Aceh Besar. These two chicken farms in Aceh contribute to food security by producing chicken eggs. Assuming a 5% mortality rate for fifty thousand laying hens (Sare and Blangstar), the mortality rate is 5%. Then capable of producing 40,000 eggs. The price offered by BTNR BLUD is only Rp. 36,000 per tray, which equates to only Rp.1200. About 20 months is the productive age of laying hens. The chicken then begins the reject stage